Inte bitch men butch - En kort queerteoretisk hjälpreda för feminister - Rosenberg, Tina (Kvinder, Køn & Forskning, 1999)
This article addresses the shortcomings of some feminist readings of queer genders. Focussing on masculinity without men, this article discusses the aesthetics and gender politics surrounding butch/femme roles within lesbian tradition. The butch/femme role-playing is excisting not because it represents heterosexual desire and gender(s), but because it does not. As a site of resistance, the butch/femme role-playing challenges heteronormativity in a society where heterosexuality is the dominant code that defines (and in a sense creates) all sexualities, no matter whether we choose to participate or not.